Drilling of carbon fibre composites: a review - Dahnel, Aishah Najiah; Barnes, Stuart; Bhudwannachai, Pipat (Trans Tech Publications Ltd., 2014)
Machining of Carbon Fibre Composite (CFC), particularly drilling is frequently employed in many industries especially when dealing with joining, assembly and structural repair of the parts. This paper summarizes the properties of the CFC as well as the appropriate material and geometry of the cutting tool that should be used when drilling of the CFC in order to optimize the drilling performance. In addition, this work also presents the literature review on the relationship between cutting speed, feed rate, tool wear, thrust force and damage of the drilled CFC. The nature and heterogeneous structure of CFC often resulted in difficulty during their machining in terms of rapid tool wear and high thrust force. As a result, this always results in the damage of the drilled parts. Furthermore, higher cutting speed and lower feed rate are also recognized as significant factors which contribute to rapid wear of the cutting tool. Therefore, the use of tungsten carbide cutting tools, cutting fluids and cryogenic machining is seen to be a practical technique in optimizing the drilling performance involving CFC. In general, this work intends to provide a basic guideline and understanding regarding drilling of the CFC.